THE DAILY ROUTINE IS THE BASIS OF A CHILD'S HEALTH - Светлана Альбертовна Дракина; Нина Константиновна Перевощикова; Наталья Степановна Черных; Тамара Михайловна Вакулова (The Publishing House Medicine and Enlightenment, 2023)
A rationally constructed and organized daily routine is the leading factor that ensures the harmonious physical and mental development of children, an optimal level of performance, preventing the development of overwork and increasing the overall resistance of the body. Purpose - analysis of the daily routine of young children on weekdays and weekends. Materials and methods. We studied the daily routine of 528 young children (average age 16.5 ± 2.7 months) for one and a half months from the moment of their admission to a preschool educational institution on weekends and on weekdays after visiting kindergarten. Before entering a preschool institution, the psychological and pedagogical parameters of the child's readiness to enter a preschool educational institution were determined (Pechory K.L., Pantyukhina G.V., Golubeva L.G.). During the period of adaptation to kindergarten, an assessment was made of the emotional profile of preschool children (up to 3 years old) when adapting to the conditions of kindergarten (Studenkin M.I., Makarenko Yu.A., Barkan A.I.). Results and their discussions. As a result of the study, it was revealed that 73.3 % of children from 1 year to 2 years were not ready to enter a preschool educational institution, almost every fourth child is conditionally ready (26.7 %). Compliance with the daily routine corresponding to the regime moments in the preschool educational institution was observed only in every third family. The result of gross violations of the daily routine in the first days of the child's stay in the preschool educational institution was sleep disturbance, which led to the formation of stress. The most pronounced negative changes in the child's emotional and behavioral reaction were recorded according to such indicators as social contacts, fear, sleep, appetite, negative and positive emotions. Positive dynamics in terms of social contacts were observed by the end of the third week of children's stay in the preschool educational institution, fear and appetite - by the 15th day, sleep - by the end of the 40th day of observation. Negative emotions began to disappear by the end of the 30th day of visiting the preschool educational institution, positive emotions began to appear by the end of the second week of stay in the preschool educational institution. Thus, the general adaptation of 12.1 % of children was favorable, almost every third child was conditionally favorable, and every second child was unfavorable. Conclusions. Thus, violations of routine moments in young children during the period of admission to preschool educational institutions underlie disorders of psycho-emotional behavior, which is a reflection of the stressful state of the child's body.